Polyphosphate in Neonates: Less Shedding from Platelets and Divergent Prothrombotic Capacity Due to Lower TFPI Levels - Schlagenhauf, Axel; Haidl, Harald; Pohl, Sina; Weiss, Eva-Christine; Leschnik, Bettina; Gallistl, Siegfried; Muntean, Wolfgang (Frontiers in Physiology, 2017)
Background: The neonatal hemostatic system exhibits a fragile balance featuring lower levels of clotting factors as well as inhibitors. Neonatal platelets show in-vitro hypoaggregability, but neonates exhibit well-functioning primary and secondary hemostasis despite this impairment. Recently, polyphosphate shed by activated platelets has been shown to induce a prothrombotic shift on the plasmatic coagulation system of adults. The impact of platelet derived polyphosphate might differ in neonates due to aforementioned peculiarities. Aims: We aimed to comparatively determine polyphosphate content and release from adult and neonatal platelets, and to determine its impact on thrombin generation in plasma from adult and cord blood. Methods: Polyphosphate was extracted from adult and neonatal platelet lysates and releasates using silica spin-columns and quantified with a DAPI based fluorescence assay. The impact of exogenous polyphosphate in various concentrations (208-0.026 µg/ml) on thrombin generation was evaluated in plasma from adult and cord blood, and in adult plasma with reduced tissue factor pathway inhibitor (TFPI) levels using calibrated automated thrombography. Results: Polyphosphate content was comparable in both groups, but the fraction of released polyphosphate upon stimulation with thrombin receptor activating peptide was lower in neonatal samples (adult: 84.112.9%; cord: 58.811.2%). Relative impact of polyphosphate on lag time of thrombin generation was higher in adult samples compared to samples from cord blood (adult: 41,0% [IQR: 35,2-71,8%] of vehicle; cord: 73,4% [IQR: 70,2-91,4%] of vehicle). However, in samples from cord blood lower concentrations of polyphosphate were required to obtain maximal impact on thrombin generation (adult: 26 µg/ml; cord: 0,814 µg/ml). PolyP affected thrombin generation in adult plasma similarly to cord plasma, when the TFPI concentration was reduced to neonatal levels. Conclusion: Differences in the impact of polyphosphate on adult and neonatal coagulation are largely caused by differences in TFPI levels. Lower polyphosphate release from neonatal platelets, but lower optimum concentration to drive neonatal plasmatic hemostasis emphasizes the well-matched, but fragile interplay between platelets and coagulation in newborns. A potential developmental mismatch should be considered when transfusing adult platelets into neonates.